KAJIAN SYAIR PADA WARAHAN KLASIK TENTANG GAMOLAN INSTRUMEN MUSIK TRADISIONAL LAMPUNG - Hasyimkan, Hasyimkan; Barnawi, Erizal; Hakim, Uswatul (IAIIG Cilacap, 2020)
Gamolan is a traditional Lampung musical instrument, Gamolan came from West Lampung which was influenced by African, Arabic, Indian, Chinese and European cultures, as well as Sumatra. Gamolan comes from the word begamol which means gathering which has three poems about gamolan including the story of warahan Radin Jambat, the oral literature of the Pubian and Tanggamus people.This research answers the problem of how classical gamolan poetry in Lampung. The goal is to be missed background gamolan poetry. The method used is descriptive qualitative analysis with the expected results that books can be made, submitted to journals and obtained copyright.